CrossMDA2: Uma abordagem para minimizar o problema da fragilidade de pointcuts na evolução de sistemas orientados a aspectos - Fernandes, Victor Hugo de Carvalho (2009)
This work proposes a model based approach for pointcut management in the presence of evolution in aspect oriented systems. The proposed approach, called conceptual visions based pointcuts, is motivated by the observation of the shortcomings in traditional approaches pointcuts definition, which generally refer directly to software structure and/or behavior, thereby creating a strong coupling between pointcut definition and the base code. This coupling causes the problem known as pointcut fragility problem and hinders the evolution of aspect-oriented systems. This problem occurs when all the pointcuts of each aspect should be reviewed due to any software changes/evolution, to ensure that they remain valid even after the changes made in the software. Our approach is focused on the pointcuts definition based on a conceptual model, which has definitions of the system's structure in a more abstract level. The conceptual model consists of classifications (called conceptual views) on entities of the business model elements based on common characteristics, and relationships between these views. Thus the pointcuts definitions are created based on the conceptual model rather than directly referencing the base model. Moreover, the conceptual model contains a set of relationships that allows it to be automatically verified if the classifications in the conceptual model remain valid even after a software change. To this end, all the development using the conceptual views based pointcuts approach is supported by a conceptual framework called CrossMDA2 and a development process based on MDA, both also proposed in this work. As proof of concept, we present two versions of a case study, setting up a scenario of evolution that shows how the use of conceptual visions based pointcuts helps detecting and minimizing the pointcuts fragility. For the proposal evaluation the Goal/Question/Metric (GQM) technique is used together with metrics for efficiency analysis in the pointcuts definition